2019
DOI: 10.1111/jfb.13866
|View full text |Cite
|
Sign up to set email alerts
|

Variation in thermal tolerances of native freshwater fishes in South Africa's Cape Fold Ecoregion: examining the east–west gradient in species' sensitivity to climate warming

Abstract: The Cape Fold Ecoregion (CFE) is a biodiversity hotspot with high levels of endemism in its freshwater fish fauna. This study examined inter and intra-specific variation in critical thermal maxima (T Cmax ) for eight native species of freshwater fish from the CFE. Cape galaxias Galaxias zebratus, Breede River redfin Pseudobarbus burchelli, Berg River redfin Pseudobarbus burgi, Clanwilliam redfin Pseudobarbus calidus and fiery redfin Pseudobarbus phlegethon were the most thermally sensitive (T Cmax = 29.8-32.8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…In conclusion, we find evidence of limited acclimation ability in the species included in this study, similar to what has been found for other aquatic species in the region (Dallas and Rivers-Moore, 2018;Reizenberg et al, 2019). The variation among species found in lower thermal limits could be explained by phylogeny and ecoregion.…”
Section: Tablesupporting
confidence: 88%
“…In conclusion, we find evidence of limited acclimation ability in the species included in this study, similar to what has been found for other aquatic species in the region (Dallas and Rivers-Moore, 2018;Reizenberg et al, 2019). The variation among species found in lower thermal limits could be explained by phylogeny and ecoregion.…”
Section: Tablesupporting
confidence: 88%
“…It is possible that S. calidus, being more uniformly distributed across the longitudinal span of the Rondegat River, is more adapted metabolically (i.e. having a thermal optimum for activity) to the mean temperature profile of the river (Reizenberg et al 2019) upon which the holding and lower test trials were based. Given this possible thermal advantage over L. seeberi at low prey densities, the difference in attack parameters can be partially explained.…”
Section: Discussionmentioning
confidence: 99%
“…Fish were introduced slowly to laboratory holding aquaria (dimensions: 900 mm × 380 mm × 330 mm) over a 12 h period to allow for acclimation to conditions in captivity and fed ad libitum on flake food and frozen chironomids. The laboratory was kept at a constant temperature of 18 °C based on long-term data collected by Reizenberg et al (2019) and temperature loggers deployed in the Rondegat River. The study species are likely adapted or acclimated to a mean temperature of approximately 18 °C based on long-term temperature data and are likely able to withstand high daily fluctuations in temperature, with most CFE species having upper thermal tolerances of 32-33 °C (Reizenberg et al 2019).…”
Section: Sampling and Holding Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences in thermal sensitivity observed in the current study for these two species could suggest that they have different thermal performance ranges, based on their different habitats. Certainly previous studies from freshwater environments have demonstrated that thermal history associated with habitat or geographic cline can be a driver of variation in thermal sensitivity even within populations of a single species (Chrétien and Chapman 2016;Reizenberg et al 2018), and the fact that changes in ocean temperature can influence the selection of different habitats by species (Freitas et al 2016). To our knowledge, however, there have be no previous investigations of inter-habitat differences in the thermal sensitivity of closely-related, reef-associated species.…”
Section: Discussionmentioning
confidence: 99%